My favourite prophet Muhammad (PBUH) stories - Saniyasnain Khan (New Delhi Goodwords, 2013)
My Favorite Prophet Muhammad Stories relates fascinating stories about the Kabbah and how the pilgrimage to it and trade with far-off lands such as Yemen, Syria, Iraq, Persia were organized along the silk route by the Prophet$1 (Bs great grandfather. Everything is covered from the re-digging of the Mazama well to the year of elephants, to the birth of the Prophet Muhammad, and then on to his childhood in the desert and his early life in Markka. This book encourages children to discover for themselves the message of the life of the Prophet and to find their own ways of applying the Prophet$1 (Bs timeless teachings to their lives.s
This beautifully illustrated children$1 (Bs book presents some of the most loved stories from the life of Prophet Muhammad (peace be upon him) in a simple and engaging style. Designed to inspire young readers, the book highlights the Prophet$1 (Bs noble character, kindness, honesty, and compassion through carefully selected events from his life. Each story is written in clear language with colourful artwork to capture the attention of children and encourage them to learn about Islamic values.s